Initial and Planning Stages in Preservation Process, Contributions to Recommendation for Appropriate Conservation Treatments: A Case of Conservation of the Our Lady of the Rosary Church Project - Issarathumnoon, Wimonrart (NAJUA: Architecture, Design and Built Environment, 2018)
This paper aims at understanding advantages of applying preservation process based on international doctrines to preservation practices in Thailand. The Conservation of the Our Lady of the Rosary Church Project that has been conducted based on such process was used as a case study. The project showed that the process of preparing a conservation plan helped to assemble important data covering a deeper understanding of the historic building’s evolution over time as well as a better understanding of its heritage significances and its current specific circumstances. This information led to appropriate conservation treatments and conservation works.